Analisis faktor-faktor yang mempengaruhi pola konsumsi rumah tangga petani sayur di Kabupaten Muaro Jambi (Studi Kasus Desa Mekar Jaya Kecamatan Sungai Gelam) - Agnes Lestari Simanulang; Rahma Nurjanah; Putri Intan Suri (PT. Saha Kreasi Indonesia, 2025)
This study aims to identify and analyze the socioeconomic characteristics of vegetable farmers in Muaro Jambi Regency (a case study of Mekar Jaya Village, Sungai Gelam District) and to identify and analyze the factors influencing the consumption patterns of vegetable farmer households in Muaro Jambi Regency (a case study of Mekar Jaya Village, Sungai Gelam District). The research method used in this study was a survey with a quantitative approach. Data were obtained through direct interviews with 43 vegetable farmer households at the study site. The results showed that the average age of vegetable farmers was 48 years, with the majority being male. The average land area owned by vegetable farmers was 178 m², with an average farming experience of 15 years. The average income was Rp 3,250,000 per month, with an average family size of four people. Income and number of family members positively and significantly influenced the consumption patterns of vegetable farmer households, while education had no significant effect.